Radicular Pain from Lumbar Canal Stenosis in Addition to Pre-Existing Phantom Limb Pain - Tomasi, S. O.; Ghani, I.; Waldvogel, D.; Hausmann, O. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Phantom limb (PL) is a term used to designate the sensation of the presence of an extremity following amputation, and it may be seen immediately after injury or years later in the part of the body that is deafferented or amputated. Phantom limb pain (PLP) is the term used to describe painful sensations referred to the absent limb. We present a case of a 71-year-old male with spinal claudication from discoligamentous lumbar canal stenosis L3–L4 and L4–L5 with L5 radicular pain in the left PL 13 years after the amputation. The patient had a disappearance of his radicular pain in the left PL following microsurgical lumbar decompression of L3–L4 and L4–L5. This is one of the rare cases reported in the literature in which a radicular pain in the PL disappeared following surgical decompression of the spinal canal.
Keywords: phantom limb; radicular pain; spinal stenosis